MANAGEMENT OF NATIONAL DEFENSE AND SECURITY EDUCATION IN THE STRATEGY OF EARLY AND REMOTE HOMELAND PROTECTION - SOME THEORETICAL AND PRACTICAL ISSUES - Bui Van Hung (Tạp chí Khoa học, 2025)
In the complex and unpredictable developments in the global and regional situation, the Party and the State of Vietnam identified the early and remote homeland protection strategy as a key orientation to ensure national defense and security in the current period. National Defense and Security Education (NDSE) plays a crucial role in raising awareness, fostering a sense of responsibility, and enhancing the readiness of the younger generation - especially students - to safeguard the Fatherland. This article focuses on analyzing fundamental theoretical issues related to the management of NDSE within the early and remote homeland protection strategy framework. It also assesses the current state of NDSE management at higher education institutions and NDSE centers. Based on this assessment, the article identifies limitations and shortcomings in the organization, coordination, and implementation of policies. It proposes several solutions to improve the effectiveness of NDSE management, meeting the requirements of higher education reform and national defense tasks in the new context.